Analysis of extemporaneous oral liquid from commercially available drugs in hospital - Jhohann Richard de Lima Benzi; Patrícia De Carvalho Mastroianni
ABSTRACT The objective of this study was to identify drugs that received dose adjustments (DA) and pharmaceutical alternatives (PA) that avoid DA, and calculate the economic percentage of this replacement. A descriptive, observational and cross-sectional study was performed in a second level hospital. The pharmacy and nursing services was accompanied to identify the drugs that received DA and the compounding techniques. After identifying all the drugs that received DA, was identified in the Brazilian market the corresponding pharmaceutical alternative, with the Drugs Price List of Brazilian Health Regulatory Agency. For those drugs that was not available any PA, was performed a research of studies that describe compounding techniques in international scientific databases. Was identify 88 drugs that received DA, and these, 50 do not have any PA. Were identified compounding techniques to 40 drugs. Although any drug has your own particularity of compounding, the compounding techniques can be grouped in five categories. The standardization of 29 drugs can reduce in 28% the DA procedure and cost saving of 34,85%/month. We can conclude that every three drugs prescribed, one received DA and every three DA, one can be avoided by the selection of 29 PA, saving cost as well. The use and standardization of five techniques would attend the pharmaceutics recommendations for better dissolution, bioavailability and patient safety.